KEMAMPUAN PEMECAHAN MASALAH SISWA PADA TOPIK SUHU DAN KALOR MELALUI PEMBELAJARAN COGNITIVE APPRENTICESHIP - Imam Maksum Al Maliki; Arif Hidayat; Sutopo Sutopo (Pascasarjana Universitas Negeri Malang, 2017)
Problem solving ability is one of the necessary abilities of students in studying physics. Therefore, these capabilities need to be taught to students in a variety of topics. This study aims to explore the students' problem solving ability on heat and temperature through cognitive apprenticeship learning. Subjects in this study were 19 students of class C2 XMIPA SMAN 9 Malang academic year 2015/2016. The research method used was embedded mixed-method experimental models. The results showed: (1) The students' problem solving ability has increased significantly with the average N-Gain score of 0.53 (medium category), and the value of the effect size was -2.57 (very strong category); (2) The students' problem solving ability in general have a positive change in phase useful description, physics approach, mathematical procedures, and logical progression. Kemampuan pemecahan masalah merupakan salah satu kemampuan yang diperlukan siswa dalam mempelajari fisika. Oleh karena itu, kemampuan tersebut perlu diajarkan kepada siswa dalam berbagai topik. Penelitian ini bertujuan untuk mengeksplorasi kemampuan pemecahan masalah siswa pada topik suhu dan kalor melalui pembelajaran cognitive Apprenticeship. Subjek dalam penelitian ini adalah 19 siswa kelas XMIPA C2 SMAN 9 Malang tahun akademik 2015/2016. Metode penelitian yang digunakan adalah mixed method embedded experimental design. Hasil penelitian menunjukkan (1) kemampuan pemecahan masalah siswa mengalami peningkatan signifikan dengan N-Gain skor rata-rata sebesar 0,53 (kategori sedang), dan nilai effect size sebesar -2.57 (kategori sangat kuat); (2) Kemampuan pemecahan masalah siswa mengalami perubahan positif pada tahap useful description, physics approach, mathematical procedure, maupun logical progression.